Kesan penggunaan aplikasi Plickers dalam pembelajaran topik imbuhan berasaskan gamifikasi terhadap pelajar tahun - Tan, Cheng Rui (2021)
The purpose of this study is to examine the effect of the use of Plickers application in the learning of year three topic “imbuhan meN-” based on gamification on student motivation, achievement, and perception. The design of this study was an experimental one-group pretest - posttest design. 30 primary school students from national type primary schools in Skudai, Johor were selected by random cluster sampling to be involved in this study. The instruments used to collect the data were pre-test and post-test, 5-point Likert scale IMMS (Instructional Materials Motivation Survey) questionnaire and interviews. Findings of the study on student motivation found that, attention (4.50), relevance (4.58), confidence (3.89) and satisfaction (4.70) obtained a mean exceeding 3.5. There were 29 students received a mean score at least 3.50 or above. The findings of the study show that almost all students have a high level of motivation. The findings of the study also found that students obtained an average score of 70.33 in the pre-test and 79.57 in the post-test. The result of paired sample t test also indicated there was a significant difference student’s performance before after students used Plickers application, p<0.05. The effect size of this study also stated that the treatment in this study had a large effect on the students with the value, d = 1.061. Furthermore, the interview results also showed that the students had a positive perception towards the use of Plickers application. The word "fun" was mentioned 7 times and the phrase "playing cards" was also mentioned 6 times by students in the interview. In conclusion, the use of Plickers application has had a positive impact on student motivation, achievement, and perception. The use of Plickers applications based on gamification has the potential to be implemented in teaching and learning in schools.